Systemic Toxicity of Intraperitoneal Vancomycin - Teerath Kumar; Iris Teo; Brendan B. McCormick (Case Reports in Nephrology)
Intraperitoneal vancomycin is used for empiric treatment of peritoneal dialysis peritonitis. It is dosed intermittently and a high systemic concentration is often achieved. Despite this, there are very few reports of systemic toxicity from intraperitoneal vancomycin. We report the course of a patient who developed a drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome after three weeks of intraperitoneal vancomycin. We review the literature and conclude that this is the first ever reported case of DRESS syndrome from intraperitoneal vancomycin.